Pengaruh Terapi Murotal Surat Ar-Rahman Terhadap Tingkat Kecemasan Ibu Bersalin Kala I Fase Aktif Di BPM Rika Rohaeni S.ST Kecamatan Muncang Kabupaten Lebak : The Effect of Murotal Surah Ar-Rahman Therapy on the Anxiety Level of Mothers in the First Stage of Active Phase at BPM Rika Rohaeni S.ST, Muncang District, Lebak Regency - Herwati, Novi Dewi (Dohara POAJ, 2023)
Introduction: The feeling of anxiety for the mother in labor when thinking about the process of giving birth and the condition of the baby to be born does not only occur in her first pregnancy; but also, in subsequent pregnancies. Some actions that can be taken to overcome anxiety in pregnant women include using pharmacological and non-pharmacological therapies. In this study, researchers took action to overcome anxiety in mothers in the first stage of labor, one of which was the distraction technique, one of which was murotal therapy. Methods: The research design used was one group pre and post-test without a control group design, the sample of this study was 30 people. Results: The results of the average value of maternal anxiety during the first active phase before being given murotal surah Ar-Rahman therapy was 47,733; the minimum value was 33,0 the maximum value was 64,0 and the standard deviation was 8,582 (p-value = 0,015); while the average anxiety for mothers in labor. when 1 active phase after being given murotal surah Ar-Rahman therapy was 44,333 the minimum value was 30,0 the maximum value was 59,0 and the standard deviation was 7,866. The results of the Wilcoxon test showed the effect of giving murotal surah Ar-Rahman therapy on the anxiety level of mothers during the first active phase of childbirth at BPM Rika Rohaeni S.ST Muncang District, Lebak Regency in 2023 (p-value = 0,000). Discussion: Murotal therapy affects maternal anxiety so it is hoped that health workers can combine pharmacological and non-pharmacological therapy as a form of intervention in providing midwife services.